Strategies to decrease social jetlag: Reducing evening blue light advances sleep and melatonin. (13th December 2018) - Zerbini, Giulia; Kantermann, Thomas; Merrow, Martha
Abstract: The timing of sleep is under the control of the circadian clock, which uses light to entrain to the external light‐dark cycle. A combination of genetic, physiological and environmental factors produces individual differences in chronotype (entrained phase as manifest in sleep timing). A mismatch between circadian and societal (e.g., work) clocks leads to a condition called social jetlag, which is characterized by changing sleep times over work and free days and accumulation of sleep debt. Social jetlag, which is prevalent in late chronotypes, has been related to several health issues. One way to reduce social jetlag would be to advance the circadian clock via modifications of the light environment. We thus performed two intervention field studies to describe methods for decreasing social jetlag. One study decreased evening light exposure (via blue‐light‐blocking glasses) and the other used increased morning light (via the use of curtains). We measured behaviour as well as melatonin; the latter in order to validate that behaviour was consistent with this neuroendocrinological phase marker of the circadian clock. We found that a decrease in evening blue light exposure led to an advance in melatonin and sleep onset on workdays. Increased morning light exposure advanced neither melatonin secretion nor sleep timing. Neither protocol led to a significant change in social jetlag. Despite this, our findings show that controlling light exposure at home can be effective in advancing melatonin secretion and sleep, thereby helping late chronotypes to better cope with early social schedules. Abstract : Social jetlag (SJL) is a measure of the discrepancy between circadian (internal) and social (external) clocks. SJL has been associated with widespread, population diseases. Here we tested two protocols involving in‐home light interventions in order to reduce SJL. We found that decreasing evening blue light advanced sleep onset and melatonin secretion, however, SJL was not reduced.